Computing behind the iron curtain and beyond hungarian national perspective - Raffai, Maria (2006)
At the beginning of the computing era it was a great challenge to write a running program in order to solve different mathematical, statistical tasks, and to get the appropriate results by using a computer. At the university where I had began my studies we started to get acquainted with computers using a Russian made machine, named URAL 2. Looking back to the roots and thinking of the Hungarian born pioneer of computer science: the polymath John von Neumann, I had intended to deal with the history of computing at the very beginning of the eighties. Although there is a wide range of computing history literature worldwide (most of them in English), there are not any publications dealing with the Hungarian results. As I was one of the first graduates on computing taught by the Pioneers, I am forced to perform research on all materials dealing with the Hungarian achievements in computing, to protect the values of the past as long as it is not too late and also to make the results known!